HUBUNGAN KELUARGA SADAR GIZI DENGAN STATUS GIZI BALITA DI DESA MOPUYA SELATAN KECAMATAN DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Muliati, Dwi Deni; Ismanto, Amatus Yudi; Malara, Reginus (JURNAL KEPERAWATAN, 2014)
Abstract: Introduction: Nutritional status of children under five is health generated by a balance between the needs and input of nutrients. Assessment of nutritional status using anthropometry, in this study measured as Weight Loss by Age z-score formula based on the NCHS. One of the health problems in the world due to lack of nutrition is the death of children. Data in Indonesia showed that children under five years of age who suffered as much as 19.6% underweight, deaths of children fewer than 5 years were 39 per 1,000 live births. Children under five suffering malnutrition in rural South Mopuya much as 8 toddlers. This study aims to determine the relation of nutrition conscious family (Kadarzi) with Toddler Nutritional Status in Southern Mopuya North Dumoga Bolaang Mongondow District. Method: This type of research is an analytical survey with cross sectional approach. The technique of collecting sampling was done through purposive sampling. The samples in this study were 62 respondents consisted of children under five and mothers. Results: of the chi-square statistical test obtained p value 0.006 is smaller than Î± = 0.05. Discussion: It can be concluded that there is a relation of Nutrition Conscious Family (Kadarzi) with Toddler Nutritional Status in Southern Mopuya North Dumoga Bolaang Mongondow District. This research is expected as local health centers can improve the work program to address the problem under nutrition. Keywords: Kadarzi, nutritional status, toddlers Abstrak: Pendahuluan: Status gizi balita adalah status kesehatan balita yang di hasilkan oleh keseimbangan antara kebutuhan dan masukan zat gizi. Penilaian status gizi dapat menggunakan Antropometri, dalam penelitian ini di ukur berdasarkan Berat Badan menurut Umur berdasarkan rumus z-score NCHS. Salah satu permasalahan kesehatan di dunia akibat kurangnya gizi adalah kematian anak balita. Data di Indonesia menunjukkan bahwa balita yang mengalami underweight sebanyak 19.6%, kematian anak dibawah 5 tahun sebanyak 39 per 1000 kelahiran hidup. Balita yang mengalami gizi kurang di Desa Mopuya Selatan sebanyak 8 Balita. Penelitian ini bertujuan untuk mengetahui hubungan Keluarga Sadar Gizi (Kadarzi) dengan Status Gizi Balita di Desa Mopuya Selatan Kecamatan Dumoga Utara Kabupaten Bolaang Mongondow. Metode: Jenis penelitian ini ialah survey analitik dengan pendekatan cross sectional. Tekhnik pengambilan sampel secara purposive sampling. Sampel dalam penelitian ini sebanyak 62 responden terdiri dari anak dan ibu balita. Hasil: uji statistik chi square diperoleh nilai p 0,006 lebih kecil dari Î±=0,05. Pembahasan: terdapat hubungan Keluarga Sadar Gizi (Kadarzi) dengan Status Gizi Balita di Desa Mopuya Selatan Kecamatan Dumoga Utara Kabupaten Bolaang Mongondow. Diharapkan pelayanan kesehatan setempat dapat meningkatkan program kerja untuk mengatasi masalah gizi kurang. Kata Kunci : Kadarzi, Status gizi, Balita